Targeting Echinococcus multilocularis stem cells by inhibition of the Polo-like kinase EmPlk1. - Andreas Schubert; Uriel Koziol; Katia Cailliau; Katia Cailliau; Mathieu Vanderstraete; Colette Dissous; Klaus Brehm (Public Library of Science (PLoS), 2014)
Alveolar echinococcosis (AE) is a life-threatening disease caused by larvae of the fox-tapeworm Echinococcus multilocularis. Crucial to AE pathology is continuous infiltrative growth of the parasite's metacestode stage, which is driven by a population of somatic stem cells, called germinative cells. Current anti-AE chemotherapy using benzimidazoles is ineffective in eliminating the germinative cell population, thus leading to remission of parasite growth upon therapy discontinuation.We herein describe the characterization of EmPlk1, encoded by the gene emplk1, which displays significant homologies to members of the Plk1 sub-family of Polo-like kinases that regulate mitosis in eukaryotic cells. We demonstrate germinative cell-specific expression of emplk1 by RT-PCR, transcriptomics, and in situ hybridization. We also show that EmPlk1 can induce germinal vesicle breakdown when heterologously expressed in Xenopus oocytes, indicating that it is an active kinase. This activity was significantly suppressed in presence of BI 2536, a Plk1 inhibitor that has been tested in clinical trials against cancer. Addition of BI 2536 at concentrations as low as 20 nM significantly blocked the formation of metacestode vesicles from cultivated Echinococcus germinative cells. Furthermore, low concentrations of BI 2536 eliminated the germinative cell population from mature metacestode vesicles in vitro, yielding parasite tissue that was no longer capable of proliferation.We conclude that BI 2536 effectively inactivates E. multilocularis germinative cells in parasite larvae in vitro by direct inhibition of EmPlk1, thus inducing mitotic arrest and germinative cell killing. Since germinative cells are decisive for parasite proliferation and metastasis formation within the host, BI 2536 and related compounds are very promising compounds to complement benzimidazoles in AE chemotherapy.